An Analysis Of Freestyle Swimming Technique on Students the Physical Education, Health And Leisure Study Program - Rezki, Rezki; Zulkifli, Zulkifli; Jatra, Rices; Aprianti, Lisa (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2022)
The purpose of the study. The purpose of this study is to describe the technique of freestyle swimming in terms of: body position, hand movements, foot movements, breath taking movements and movement coordination. Materials and methods. Determine the level of mastery of the freestyle swimming technique in the students of the Physical Education Study Program at the Universitas Pahlawan who attend basic swimming lectures. Is it classified as very good, good, less or less. This research is descriptive, the population of this research is 20 students. Results. the level of mastery of technique on the body position indicator is 66% and the error rate is 34%, then the hand rotation indicator is 66 % and the error rate is 34%, then the foot movement indicator (Kicking) is 70% and the error rate is 30%. Furthermore, the level of mastery of techniques in breathing (breating) is 68.5% and the error rate is 30%, then the level of mastery of techniques in coordination is 68.5% and the error rate is 31.5%. Conclusions. Concluded that the level of mastery of technique on each indicator of the freestyle swimming technique